Peran Program Dinas Koperasi dan UKM dalam Pemberdayaan dan Pengembangan UMKM di Kota Binjai - Salsabilla Salsabilla; Nurul Jannah; Lathief Ilhamy Nasution (Owner : Riset dan Jurnal Akuntansi, 2025)
ABSTRACT This study aims to analyze the role of the Cooperative and SME Agency program in the empowerment and development of Micro, Small, and Medium Enterprises (MSMEs) in Binjai City. The scope of the study covers programs that have been implemented, implementation efforts, and obstacles faced by the agency and MSME actors. This study uses a qualitative approach with a field study type. Data collection techniques include observation, documentation, and interviews, which are then analyzed using the Miles and Huberman interactive model. The results of the study show that the Binjai City Cooperative and SME Office has implemented various programs such as entrepreneurship training, business equipment assistance, assistance in obtaining a Business Identification Number (NIB), and MSME exhibitions. However, budget constraints and the absence of honoraria are obstacles to implementing the program. It was also found that some business actors are not yet members of the MSME community and therefore do not receive the benefits of the program. This study has both theoretical and practical implications. Theoretically, the study reinforces the understanding that the role of local government, particularly the Cooperative and SME Agency, is a strategic factor in promoting MSME empowerment through the implementation of structured programs. Practically, this study provides input for local governments to prioritize budget allocation efficiency, expand digital-based information channels, and build inclusive systems so that MSME actors outside the formal community can also benefit from the program. Keywords: MSME Empowerment, MSME Development, Cooperative and SME Agency Programs, Program Management